Self-poisoning with metaldehyde. Issue 6 (22nd May 2008) - Bleakley, C; Ferrie, E; Collum, N; Burke, L
Abstract : Metaldehyde poisoning is rare. This case report details the largest toxic dose of self-poisoning with metaldehyde ever recorded in the literature to the authors' knowledge, the aim being to emphasise the features of metaldehyde toxicity and the potential for good clinical outcome. The patient was admitted unconscious with features consistent with poisoning. Appropriate critical care was instituted early with correction of his acid-base disorder, ventilatory support, correction of haemodynamic instability, anticonvulsant therapy and early admission to the critical care unit. An almost complete recovery was seen over the following weeks, the only lasting deficit being to short-term memory, a finding common to other reported incidents of metaldehyde toxicity. This case is notable in that the patient took more than one and a half times what is considered to be a lethal dose of metaldehyde (the largest reported), but has had a remarkably good clinical outcome that is proposed to be due to methodical and timely interventions delivered according to basic principles irrespective of the absence of the early identification of the poison. The case demonstrates several of the key features of metaldehyde toxicity and the emergency management of such a situation. The published literature pertaining to metaldehyde overdose is reviewed.